2009
DOI: 10.1002/mrc.2536
|View full text |Cite
|
Sign up to set email alerts
|

New oxidized sterols from Aspergillus awamori and the endo‐boat conformation adopted by the cyclohexene oxide system

Abstract: Two new oxidized sterols 1 and 2 were obtained from the active fraction of a mangrove fungus Aspergillus awamori isolated from the soils around the mangrove plant Acrostichum speciosum. Their structures were elucidated using spectroscopic methods as 22E-7alpha-methoxy-5alpha,6alpha-epoxyergosta-8(14),22-dien-3beta-ol (1) and 22E-3beta-hydroxy-5alpha,6alpha,8alpha,14alpha-diepoxyergosta-22-en-7-one (2). The NMR data and complete assignments for both DMSO-d(6) and CDCl(3) were given. Their cytotoxic activity aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 27 publications
(17 reference statements)
2
25
0
Order By: Relevance
“…All compounds exhibited mild cytotoxic activity against B16 and SMMC-7721 cell lines. Further analysis yielded the two new oxidized sterols, (22 E )-7α-methoxy-5α,6αepoxyergosta-8(14),22-dien-3β-ol ( 180 ) and (22 E )-3β-hydroxy- 5α,6α,8α,14α-diepoxyergosta-22-en-7-one ( 181 ) which were mildly cytotoxic towards the lung cancer cell line A549 [115]. Conformational analysis on the basis of the observed NOEs in the ROESY spectrum indicated that the cyclohexene oxide system in ring B of 180 adopted an endo -boat rather than a half-chair conformation.…”
Section: Examples Of Terpenoidsmentioning
confidence: 99%
“…All compounds exhibited mild cytotoxic activity against B16 and SMMC-7721 cell lines. Further analysis yielded the two new oxidized sterols, (22 E )-7α-methoxy-5α,6αepoxyergosta-8(14),22-dien-3β-ol ( 180 ) and (22 E )-3β-hydroxy- 5α,6α,8α,14α-diepoxyergosta-22-en-7-one ( 181 ) which were mildly cytotoxic towards the lung cancer cell line A549 [115]. Conformational analysis on the basis of the observed NOEs in the ROESY spectrum indicated that the cyclohexene oxide system in ring B of 180 adopted an endo -boat rather than a half-chair conformation.…”
Section: Examples Of Terpenoidsmentioning
confidence: 99%
“…In order to study the bioactive constituents of A. amoiensis, a chemical investigation was carried out and led to the isolation of one new compound, named amauroamoienin (1), along with thirteen known compounds (2-14) (l " Fig. 1), 4-hydroxy-17methylincisterol (2) [11], (l7R)-17-methylincisterol (3) [12], 1,5dihydroxy-6′,6′-dimethylpyrano[2′,3′: 3,2] xanthone (4) [13], jacareubin (5) [13], ergosterol peroxide (6) [14], ergosta-7,22-dien-3β-ol (7) [15,16], (22E,24R)-ergosta-8,22E-diene-3β,5α,6β,7αtetraol (8) [17,18], 22E-7α-methoxy-5α,6α-epoxyergosta-8 (14),22-dien-3β-ol (9) [19], 3β,5α,9α-trihydroxyergosta-7,22-dien-6-one (10) [20,21], 1H-indole-3-carboxylic acid (11) [22], phydroxybenzoic acid (12) [23], methyl 3,4-dihydroxybenzoate (13) [24], and 7,8-dimethylalloxazine (14) [25]. Herein, we describe the isolation and structural elucidation of the new compound (1) [14] hinted that 1 had a xanthone moiety with the same structure of that of 5, which was also confirmed by olefinic and aromatic pro- , among which an epoxy group was formed based on analysis of its molecular formula.…”
mentioning
confidence: 99%
“…However, there was incorrect assignment of the protons at H-6, H-7, H-26, H-27, and H-28, as well as at some carbon atoms, as shown in Tables 2 and 3. The NMR signals of 1 were reassigned by comparison of the 1 H-and 13 C-NMR data with those of sterols having 3,7-dihydroxy-5,6-epoxy structures [6][7][8][9][10]. The corrected NMR spectral assignments for 1 are shown in Tables 2 and 3 as 1'.…”
mentioning
confidence: 99%